(untitled) (Journal of Tikapur Multiple Campus, 2022)
The public recreation parks are public goods and need timely upgrade to ensure increase public welfare. The aim of this study was to analyze the perception of the visitors on the key constructs of park service quality and estimate their willingness to pay (WTP) to access the existing public park service. Tikapur Public Park in Kailali District of Nepal was the selected study site. Regression analysis was used to identify significant variables associated with WTP. The estimated regression analysis output result shows that income level, age, years of schooling, household size, substitute site travel cost, gender, place of residence, park quality, average stay hours in the park significantly predicted the WTP of the respondent visitors. Therefore, the result shows that there is substantial space for improvement in the park to upgrade the park recreational service. Likewise, based on stated willingness to pay for the park entry fee, the existing fee is far below than their WTP. This evidence clearly indicates that TBP bestows substantial welfare to the whole society. The park management should pay enough attention upgrade quality of park. There should be comprehensive reform project to avail timely adequate park service so as to raise utility from the park.